Bequest motives among older Malays in Selangor - Shyue, Chuan Chong; Suhaili Alma’amun,; Bik, Kai Sia (Penerbit Universiti Kebangsaan Malaysia, 2015)
A bequest motive seeks to provide an economic justification for the phenomenon of intergenerational transfers of wealth. In other words, it is to explain why people leave wealth behind when they die. The objective of this study is to identify what motivates the bequest transfers among older Malays in Selangor – the largest ethnic group in Malaysia for which a bequest is culturally and religiously constructed within the society. This primary data were collected through face-to-face interviews using a structured questionnaire in the second quarter of 2011 with a total sample size of 280 older Malays aged 50 years or above in the state of Selangor. From the findings, it was discovered that older Malays in Selangor, conformed more to the altruism model than other bequest models.